2014
DOI: 10.1158/0008-5472.can-14-0110
|View full text |Cite
|
Sign up to set email alerts
|

The TGFβ–miR200–MIG6 Pathway Orchestrates the EMT-Associated Kinase Switch That Induces Resistance to EGFR Inhibitors

Abstract: While specific mutations in the tyrosine kinase domain of epidermal growth factor receptor (EGFR) identify tumors that are responsive to EGFR tyrosine kinase inhibitors (TKIs), these genetic alterations are present in only a minority of patients. Patients with tumors expressing wild-type (wt) EGFR lack reliable predictive markers of their clinical response to EGFR TKIs. Although epithelial-mesenchymal transition (EMT) has been inversely correlated with the response of cancers to EGFR-targeted therapy, the prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 41 publications
5
96
0
Order By: Relevance
“…Despite having lower EGFR activation, cells overexpressing Mig6 show higher Akt phosphorylation through activation of EGFRindependent tyrosine kinases and thereby increase their survival. Furthermore, elevated Mig6/miR-200c ratio is found to be associated with erlotinib resistance in a panel of 25 tumor cell lines and in patient-derived xenografts (PDXs) of NSCLC and pancreatic cancer [87]. Introduction of miR-200c to bladder cancer cells results in complete reversal of resistance against anti-EGFR therapies mainly through Mig6 downregulation, which in turn leads to increased surface levels of EGF receptors, thus making the anti-EGFR therapy more effective in inhibiting the signal [83].…”
Section: Mir-200c Emt and Targeted Therapy Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Despite having lower EGFR activation, cells overexpressing Mig6 show higher Akt phosphorylation through activation of EGFRindependent tyrosine kinases and thereby increase their survival. Furthermore, elevated Mig6/miR-200c ratio is found to be associated with erlotinib resistance in a panel of 25 tumor cell lines and in patient-derived xenografts (PDXs) of NSCLC and pancreatic cancer [87]. Introduction of miR-200c to bladder cancer cells results in complete reversal of resistance against anti-EGFR therapies mainly through Mig6 downregulation, which in turn leads to increased surface levels of EGF receptors, thus making the anti-EGFR therapy more effective in inhibiting the signal [83].…”
Section: Mir-200c Emt and Targeted Therapy Resistancementioning
confidence: 99%
“…Recent data showed that miR-200c negatively regulates KRAS as well, resulting in inhibition of both PI3K/Akt and MAPK pathways in breast and lung cancer cells [58,93]. TGF-β-induced expression of ZEB transcription factors downregulates miR-200c resulting in reduced EGFR activity due to upregulation of Mig6 and confers EMT [87]. On the contrary, TGF-β-induced upregulation of miR-200c has been shown in diabetic nephropathy where miR-200c targets FOG2, which is a negative regulator of the PI3K/Akt pathway [94].…”
Section: Mir-200c Regulation Of Signaling Pathwaysmentioning
confidence: 99%
“…TGF-β triggers EMT and allow the cells to become invasive (50) (Figure 2). Furthermore, transient TGF-β-stimulation induces EMT and acquired resistance to EGFR-TKIs in NSCLC cell lines (51)(52)(53). TGF-β is the most studied © Translational lung cancer research.…”
Section: Tgf-βmentioning
confidence: 99%
“…During treatment with EGFR-TKIs EMT may be initiated in the tumor cells, resembling a partial EMT. This could be caused by increased expression of TGF-β (52). Surprisingly, drug-withdrawal may further enhance the EMT state due to an EGFR-mediated boost of a partial EMT existing in a "ready-to-go" fashion (63).…”
Section: Receptor Tyrosine Kinases (Rtks)mentioning
confidence: 99%
See 1 more Smart Citation